Bank Deregulation, Competition and Economic Growth: The US Free Banking Experience - Philipp Ager; Fabrizio Spargoli (Tinbergen Institute, 2013)
We exploit the introduction of free banking laws in US states during the 1837-1863 period to examine the impact of removing barriers to bank entry on bank competition and economic growth. As governments were not concerned about systemic stability in this period, we are able to isolate the effects of bank competition from those of state implicit guarantees. We find that the introduction of free banking laws stimulated the creation of new banks and led to more bank failures. Our empirical evidence indicates that states adopting free banking laws experienced an increase in output per capita compared to the states that retained state bank chartering policies. We argue that the fiercer bank competition following the introduction of free banking laws might have spurred economic growth by (1) increasing the money stock and the availability of credit; (2) leading to efficiency gains in the banking market. Our findings suggest that the more frequent bank failures occurring in a competitive banking market do not harm long-run economic growth in a system without public safety nets.
Keywords: G18; G21; G28; N21; 330; Bank Deregulation; Bank Competition; Economic Growth; Financial Development; Dynamic Efficiency; Free Banking